(2E)-3-(4-Bromophenyl)-1-(2-methyl-4phenyl-3-quinolyl)prop-2-en-1-one - Prasath, R.; Sarveswari, S.; Vijayakumar, V.; Narasimhamurthy, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The conformation about the ethene bond [1.316 (3) angstrom] in the title compound, C(25)H(18)BrNO, is E. The quinoline ring forms dihedral angles of 67.21 (10) and 71.68 (10)degrees with the benzene and bromo-substituted benzene rings, respectively. High-lighting the non-planar arrangement of aromatic rings, the dihedral angle formed between the benzene rings is 58.57 (12)degrees.